The Fully human anti-CD47 antibody SRF231 exerts dual-mechanism antitumor activity via engagement of the activating receptor CD32a - Li Zhang; Emmanuel Normant; Ammar Adam; Marisa O Peluso; Caroline M Armet; Rachel W O’Connor; Benjamin H Lee; Andrew C Lake; Scott C Chappel; Jonathan A Hill; Vito J Palombella; Pamela M Holland; et al. (Journal for ImmunoTherapy of Cancer, 2020)
Background CD47 is a broadly expressed cell surface glycoprotein associated with immune evasion. Interaction with the inhibitory receptor signal regulatory protein alpha (SIRPα), primarily expressed on myeloid cells, normally serves to restrict effector function (eg, phagocytosis and immune cell homeostasis). CD47/SIRPα antagonists, commonly referred to as ‘macrophage checkpoint’ inhibitors, are being developed as cancer interventions. SRF231 is an investigational fully human IgG4 anti-CD47 antibody that is currently under evaluation in a phase 1 clinical trial. The development and preclinical characterization of SRF231 are reported here.Methods SRF231 was characterized in assays designed to probe CD47/SIRPα blocking potential and effects on red blood cell (RBC) phagocytosis and agglutination. Additionally, SRF231-mediated phagocytosis and cell death were assessed in macrophage:tumor cell in vitro coculture systems. Further mechanistic studies were conducted within these coculture systems to ascertain the dependency of SRF231-mediated antitumor activity on Fc receptor engagement vs CD47/SIRPα blockade. In vivo, SRF231 was evaluated in a variety of hematologic xenograft models, and the mechanism of antitumor activity was assessed using cytokine and macrophage infiltration analyses following SRF231 treatment.Results SRF231 binds CD47 and disrupts the CD47/SIRPα interaction without causing hemagglutination or RBC phagocytosis. SRF231 exerts antitumor activity in vitro through both phagocytosis and cell death in a manner dependent on the activating Fc-gamma receptor (FcγR), CD32a. Through its Fc domain, SRF231 engagement with macrophage-derived CD32a serves dual purposes by eliciting FcγR-mediated phagocytosis of cancer cells and acting as a scaffold to drive CD47-mediated death signaling into tumor cells. Robust antitumor activity occurs across multiple hematologic xenograft models either as a single agent or in combination with rituximab. In tumor-bearing mice, SRF231 increases tumor macrophage infiltration and induction of the macrophage cytokines, mouse chemoattractant protein 1 and macrophage inflammatory protein 1 alpha. Macrophage depletion results in diminished SRF231 antitumor activity, underscoring a mechanistic role for macrophage engagement by SRF231.Conclusion SRF231 elicits antitumor activity via apoptosis and phagocytosis involving macrophage engagement in a manner dependent on the FcγR, CD32a.